Atrial septal defect presenting as intractable congestive heart failure in an infant with dismal outcome: A Case report (Indian Journal of Child Health, 2021)
Congenital heart disease is a major cause of morbidity and mortality in children. We are presenting a 2-month-old infant with large ostium secundum atrial septal defect (ASD) with congestive heart failure. Isolated ASD usually does not present at this age. We are presenting this case due to unusual early presentation with isolated ASD.